The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1101/381004
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Diversity of Intrinsically Photosensitive Ganglion Cells

Abstract: 14Intrinsically photosensitive retinal ganglion cells (ipRGCs) are rare mammalian photoreceptors 15 essential for non-image-forming vision functions, such as circadian photoentrainment and the 16 pupillary light reflex. They comprise multiple subtypes distinguishable by morphology, physiology, 17 projections, and levels of expression of melanopsin (Opn4), their photopigment. The molecular 18 programs that differentiate ipRGCs from other ganglion cells and ipRGC subtypes from one 19 another remain elusive. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 122 publications
(176 reference statements)
1
7
0
Order By: Relevance
“…The OPN4‐GFP transgenic mouse line has been shown to label ipRGCs. This line, however, is reported to only visualize M1, M2, and M3 as the amount of OPN4 expression varies between the ipRGC subgroups (Berg et al., 2018). OPN4‐GFP‐positive cells colocalized with RBPMS staining (Figure 4c), and 17% ± 0% of OPN4‐GFP cells were positively labeled for Arl13b and 54% ± 7% for AC3 (Figure 4d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OPN4‐GFP transgenic mouse line has been shown to label ipRGCs. This line, however, is reported to only visualize M1, M2, and M3 as the amount of OPN4 expression varies between the ipRGC subgroups (Berg et al., 2018). OPN4‐GFP‐positive cells colocalized with RBPMS staining (Figure 4c), and 17% ± 0% of OPN4‐GFP cells were positively labeled for Arl13b and 54% ± 7% for AC3 (Figure 4d).…”
Section: Resultsmentioning
confidence: 99%
“…C57BL/6J mice were purchased from The Jackson Laboratories (stock # 000664). Genetically defined RGC transgenic mice Trhr‐GFP (Gong et al., 2003; Rivlin‐Etzion et al., 2011), Hoxd10‐GFP (Dhande et al., 2013), OPN4‐GFP (Berg et al., 2018), and Cdh3‐GFP (Osterhout et al., 2011; Quattrochi et al., 2019) were a gift from Dr. Andrew Huberman's Lab (Stanford). Mice were kept under a 12‐h light/dark cycle and had free access to food and water.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies identified 4 T-RGC and 4 F-RGC types, but this new approach revealed a fifth type within each subclass (C9 and C32, respectively; Figures 2C, 2D, and S2B). For ipRGCs, we discovered markers for M1 (C33 and 40), M2 (C31), and M4 (C43) types, including some that divide M1-RGCs (identified by high levels of Opn4 and expression of Adcyap1; Hannibal et al, 2002) into two types (M1a, M1b), as well as an additional cluster (C22) that could correspond to the morphologically and physiologically characterized M3, M5, or M6 types (Figure 2E) (Quattrochi et al, 2019;Schmidt et al, 2011;Stabio et al, 2018;Berg et al, 2019). For ooDSGCs, most of which are Cartpt+, we identified the nasal-preferring type (N-ooDSGC) by expression of Mmp17, but only a single cluster (C16) expressed Col25a1, a marker of both D-and V-ooDSGCs (Kay et al, 2011).…”
Section: Transcriptome-assisted Division Of Rgcs Into Subclassesmentioning
confidence: 99%
“…For instance, M1 ipRGCs can be distinguished by expression of adenylate cyclase activating polypeptide 1 (Adcyap1) and the absence of the neuromedin B (Nmb) gene while an additional M1 type can be identified by the co-expression of Adcyap1 and Nmb (Tran et al, 2019). M2 subtype can be identified by the presence of Spp1 and T-box transcription factor (Tbx20), known to be selectively expressed in ipRGCs and greatly enriched in M2 over other ipRGC types (Berg et al, 2019). M4/alpha ON-S RGCs were found to be distinguished by the expression of Spp1 and interleukin one receptor accessory protein like 2 (Il1rapl2) while all other ipRGC types by serpin family E member 2 (Serpine2) and cadherin related family member 1 (Cdhr1) (Tran et al, 2019).…”
Section: F-retinal Ganglion Cells (All Subtypes) and Provisionally N-...mentioning
confidence: 99%